Pendampingan Manajemen Operasional, Pemasaran Digital, dan SDM dalam Meningkatkan Inovasi dan Daya Saing UMKM Bakso Bakar Risky : Penelitian - Fiula Zusnita Hanafrida; Rahma Faizza Salsabila; Fatih Albar; Jennifer Farihatul Bait (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in driving the Indonesian economy. This sector employs more than 119 million workers, accounting for 97% of the national workforce, with a significant role coming from the food and beverage industry. This community service program aims to identify and analyze the challenges faced by the Bakso Bakar Risky MSME, located in Tugu Village, RT 04, RW 03, Mantup District, Lamongan Regency, in an effort to increase market competitiveness. Through this assistance, the Bakso Bakar Risky MSME is expected to maintain its product quality with the help of written Standard Operating Procedures (SOP), improve business performance by managing digital marketing strategies through Instagram, and determine employee recruitment decisions with the help of flowcharts. This assistance results in more consistent product presentation, a more managed Instagram, and more targeted HR decision-making.